(untitled) (Web of Teachers: Inderscience Research, 2025)
The integration of digital technologies into the educational process has revolutionized teaching and learning practices. This article explores the application of digital tools in education, highlighting their benefits, challenges, and future potential. By analyzing current literature, methodologies, and case studies, the paper provides insights into how digital technologies enhance educational outcomes and foster innovative pedagogical approaches.